Minimum ten-year follow-up of a randomized trial comparing acetabular component fixation of two porous in-growth surfaces using radiosteriometric analysis. (1st October 2020) - Rahman, Luthfur; Ibrahim, Mazin S.; Somerville, Lyndsay; Teeter, Matthew G.; Naudie, Douglas D.; McCalden, Richard W.
Abstract : Aims: To compare the in vivo long-term fixation achieved by two acetabular components with different porous ingrowth surfaces using radiostereometric analysis (RSA). Methods: This was a minimum ten-year follow-up of a prospective randomized trial of 62 hips with two different porous ingrowth acetabular components. RSA exams had previously been acquired through two years of follow-up. Patients returned for RSA examination at a minimum of ten years. In addition, radiological appearance of these acetabular components was analyzed, and patient-reported outcome measures (PROMs) obtained. Results: In all, 15 hips were available at ten years. There was no statistically significant difference in PROMS between the two groups; PROMs were improved at ten years compared to preoperative scores. Conventional radiological assessment revealed well-fixed components. There was minimal movement for both porous surfaces in translation (X, Y, Z, 3D translation in mm (median and interquartile range (IQR)), StikTite (Smith and Nephew, Memphis, Tennessee, USA): 0.03 (1.08), 0.12 (0.7), 0.003 (2.3), 0.37 (0.30), and Roughcoat (Smith and Nephew): -0.6 (0.59), –0.1 (0.49), 0.1 (1.12), 0.48 (0.38)), and rotation (X, Y, Z rotation in degrees (median and IQR), (Stiktite: -0.4 (3), 0.28 (2), -0.2 (1), and Roughcoat: - 0.4 (1), –0.1 (1), 0.2 (2)). There was no statistically significant difference between the two cohorts (p-value for X, Y, Z, 3D translation - 0.54, 0.46, 0.87, 0.55 and for X, Y, Z rotation - 0.41, 0.23, 0.23 respectively) at ten years. There was significant correlation between two years and ten years 3D translation for all components ( r = 0.81(p =< 0.001)). Conclusion: Both porous ingrowth surfaces demonstrated excellent fixation on plain radiographs and with RSA at ten years. Short-term RSA data are good predictors for long-term migration data.